2002
DOI: 10.3354/meps237159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the polychaetes Nereis diversicolor and Arenicola marina on the fate and distribution of pyrene in sediments

Abstract: Effects of the polychaetes Nereis diversicolor and Arenicola marina on the distribution, metabolism and removal of [ 14 C-4, 5, 9,10]-pyrene in sediment microcosms were studied over 42 and 53 d, respectively. Unmetabolized pyrene, water-and organic-soluble pyrene metabolites were quantified in sediment, interstitial water and overlying water, and 14 CO 2 production was also assessed. Both N. diversicolor and A. marina enhanced fluxes of sediment-associated pyrene and metabolites into overlying water but to dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 47 publications
(53 reference statements)
1
29
0
Order By: Relevance
“…Although only a few studies have examined the effects of infauna on microbial PAH degradation, most of these show that the presence of infauna such as Nereis virens, Arenicola marina and Capitella sp. stimulate the degradation of various PAHs, and enhancement factors of between 2 and 3 have been reported (Bauer et al 1988, McElroy et al 1990, Christensen et al 2002. In contrast, Kure & Forbes (1997) observed decreased mineralization of fluoranthene in a sediment containing A. marina.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Although only a few studies have examined the effects of infauna on microbial PAH degradation, most of these show that the presence of infauna such as Nereis virens, Arenicola marina and Capitella sp. stimulate the degradation of various PAHs, and enhancement factors of between 2 and 3 have been reported (Bauer et al 1988, McElroy et al 1990, Christensen et al 2002. In contrast, Kure & Forbes (1997) observed decreased mineralization of fluoranthene in a sediment containing A. marina.…”
Section: Discussionmentioning
confidence: 78%
“…The few studies examining the effects of macrobenthos on total microbial PAH mineralization indicate that this stimulation also applies to PAH degradation (Bauer et al 1988, McElroy et al 1990, Christensen et al 2002. However, decreased PAH degradation in the presence of polychaetes has also been observed due to transport of PAH-containing material from the surface into deeper anoxic zones (Kure & Forbes 1997, Banta & Andersen 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Cuny et al (2007) observed similar changes in the bacterial community due to the presence of the polychaete Nereis diversicolor in oil-polluted Eukaryotes present in the sediment are not likely to directly influence the mineralization rate of naphthalene due to the fact that contrary to many bacterial biotransformation pathways, eukaryotic biotransformation pathways do not cleave the aromatic ring structure (Cerniglia and Heitkamp, 1989). The eukaryotic biotransformation pathway functions rather as a detoxification mechanism by creating water-soluble metabolites (McElroy, 1990;Christensen et al, 2002). These metabolites have in turn been shown to be difficult to use for PAHdegrading bacteria, thereby inhibiting mineralization rather than promoting it (Giessing and Johnsen, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The persistence of PAHs in marine sediments may be influenced by benthic invertebrate bioturbation (Christensen et al, 2002;Ciarelli et al, 1999;McElroy et al, 1990). Through processes such as deposit-feeding and enhancement of microbial metabolic activity PAHs may be remobilized from the sediment compartment, and either transferred to organisms at higher trophic levels or to the overlying water column, both processes inevitably changing the bioavailability of the PAH.…”
Section: Introductionmentioning
confidence: 99%
“…N. virens is a large, benthic omnivorous polychaete, which is capable of several different feeding strategies (i.e., predation, deposit-feeding, scavenging and filter-feeding), though adults are almost exclusively carnivorous (to the extent that food is available) (Tita et al, 2000). This polychaete is an efficient biotransformer of PAHs (McElroy, 1990;Christensen et al, 2002), and has been shown to be relatively tolerant to organic contaminants (Reish and Gerlinger, 1997).…”
Section: Introductionmentioning
confidence: 99%